The association between specific types of childhood adversity and attenuated psychotic symptoms in a community sample. Issue 2 (20th September 2017) - Mongan, David; Shannon, Ciaran; Hanna, Donncha; Boyd, Adrian; Mulholland, Ciaran
Abstract : Aim: This study aimed to examine the relationship between types of childhood adversity and attenuated psychotic symptoms in a general population sample, and to determine the predictive role of other psychosocial factors such as resilience, coping style and social support. Methods: An online survey was conducted with a US‐based general population sample of 748 participants (aged 18 to 35 years) using Amazon's Mechanical Turk (an online crowd‐sourcing service). Participants completed the Adverse Childhood Experiences Questionnaire (ACE‐Q), the Prodromal Questionnaire (PQ‐16), the Brief COPE Scale, the Brief Resilience Scale (BRS), the Multidimensional Scale of Perceived Social Support and the Neighbourhood Cohesion Scale. A series of backwards stepwise hierarchical regression analyses was employed to determine the predictors of PQ‐16 score. Results: Participants reported an average of 2.99 attenuated psychotic symptoms (from a total of 16), and an average of 2.77 childhood adversities (from a total of 10). In the final model, the specific types of childhood adversity which significantly predicted PQ‐16 score were verbal abuse, sexual abuse and physical neglect. Resilience, as well as the coping styles of self‐distraction, denial, substance use, emotional support, venting, religion and self‐blame, were significant predictors; perceived social support and neighbourhood cohesion were not. This model predicted 33% of the variance in PQ‐16 score. Conclusions: The results of this study support the association between childhood adversity and attenuated psychotic symptoms in the general population. Resilience and coping styles were also important predictive factors. These data suggest potential strategies on which to focus for early intervention and prevention.